Ekstraksi Tahap Tunggal Kalium Hidroksida Dari Abu Tandan Kosong Sawit - Shinta Anggraini; Zulfansyah Zulfansyah; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The utilization from oil palm empty fruit bunches is still limited. One alternative to the utilization of oil palm empty fruit bunches is by extracting potassium hydroxide from the ashes of oil palm empty fruit bunches. This study aims to determine the effect of temperature and extraction time using the single-stage method on the yield of potassium hydroxide. The dry ash from oil palm empty fruit bunches is reashing in the furnace and sieved with a 200 mesh sieve then extracted using water as a solvent at a temperature of 70oC, 80oC, 9 oC and extraction time of 4, 5, 6 hours. Ash extraction of oil palm empty fruit bunches at 90oC and 6 hours resulted in a potassium hydroxide yield of 51.37%. The results showed that the yield of potassium hydroxide increased with increasing temperature and extraction time. Keywords: extraction, oil palm empty fruit bunch, potassium hydroxide, single-stage